Analisis Strategi Dan Feasibility Pengembangan MRO Pemeliharaan Engine Di Indonesia - Freddy Franciscus; Ericko Chandra Utama (FTK UNSURYA, 2020)
The aircraft maintenance business in Indonesia is still very attractive along with increasing number of aircraft on Indonesia airlines. As much as 65% of the aircraft maintenance costs of domestic airlines that have not been absorbed by MRO Indonesia. Most of the unabsorbed portions are aircraft engine and component maintenance clusters which only absorb about 10% (USD 100 Million) of 75% (USD 750 Million Th 2017) engine maintenance costs (35%) and aircraft components (45%), issued by Indonesian airlines. From the 10% uptake of engine maintenance costs and components, the portion of engine maintenance maintenance uptake is only 5% (USD 50 Million) of 35% (USD 350 Million) engine maintenance costs. There is still around 30% (USD 300 Million) which is an opportunity for MRO Indonesia to develop the engine maintenance capability of Indonesian airlines. Based on several types of aircraft engines in Indonesian airlines, CFM56-7B used by B737-800/900 which has the largest population of around 450 engines. From the feasibility analysis on the development of the capability of the MRO engine for maintenance of the CFM56-7B, the ROI and Pay Back Period / PBP calculations for the capability engine development program are 24.57% and 4.4 years respectively. The ROI and PBP show that the CFM56-7B MRO engine development strategy is feasible.